Learning English through Storytelling: Using Let’s Read Digital Picture Books for First Graders - Hana Ristami (Hasanuddin University, 2026)
Teaching English to first graders in EFL classroom will meet challenges because the students are still in the phase of transition from kindergarten school to elementary school. In a situation where first graders still struggle to read and write in Indonesian language, an English teacher requires an effective way to help the students be interested in learning this language. Since the characteristics of young learners are active, learn through sensory, and focus on concrete things, storytelling can be chosen to teach English for first graders. Let’s Read as a digital picture book can be used for storytelling for its beautiful illustration and levels of reading difficulty that can be adjusted based on the ages of the readers. This research aims to investigate the role of Let’s Read in helping first graders learn English through storytelling and how it boosts the students’ productive skills. The method used was case study. The participants were 18 first graders and the data was collected from classroom observation, documentation during storytelling and making a picture book, and teacher’s reflection. The results showed Let’s Read as a learning media helped young learners in learning English because of its interesting features and it boosted the students’ productive skills through a picture book making.